2021
DOI: 10.18502/ijm.v13i5.7436
|View full text |Cite
|
Sign up to set email alerts
|

Biological characteristics and anti-biofilm activity of a lytic phage against vancomycin-resistant Enterococcus faecium

Abstract: Background and Objectives: An important leading cause of the emergence of vancomycin-resistant enterococci, especially Enterococcus faecium, is the inefficiency of antibiotics in the elimination of drug-resistant pathogens. Consequently, the need for alternative treatments is more necessary than ever. Materials and Methods: A highly effective bacteriophage against vancomycin-resistant E. faecium called vB-EfmS-S2 was isolated from hospital sewage. The biological properties of phage S2 and its effect on b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 41 publications
0
6
0
Order By: Relevance
“…Isolation of phage was performed using the previously described method with slight modifications ( 21 ). The E. faecalis V583 was used as a host for phage isolation and propagation.…”
Section: Methodsmentioning
confidence: 99%
“…Isolation of phage was performed using the previously described method with slight modifications ( 21 ). The E. faecalis V583 was used as a host for phage isolation and propagation.…”
Section: Methodsmentioning
confidence: 99%
“…To explore the initial phases of infection, an absorption time assay was conducted [ 18 ]. In this experiment, mid-exponential phase VRE was subjected to exposure to the phage, with samples collected at 1-minute intervals over a 10-minute duration to monitor unabsorbed phages.…”
Section: Methodsmentioning
confidence: 99%
“…The effect of temperature on phage viability was evaluated by incubating the phage suspensions at different temperatures (-20, 4, 37, 50, 60, and 70°C) for 1h. Survival rates were determined using plaque assays [ 18 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have also shown that phages can be used to control biofilms formed by Enterococcus faecalis [23,61].…”
mentioning
confidence: 99%